MENGURAI ISU SOSIAL DALAM HAL PERKAWINAN DAN JUAL BELI: Kajian Hadis Isyarat Dalam Kitab Sunan Al-Tirmidzi - Mohammad Fattah (Reflektika, 2020)
The expertise of al-Tirmidhi in collecting the Prophetic tradition has been proven when he used the term wa fi al-bab (in this topic there is hadith) according to narrators among the companions. However, these indicative hadiths were failed to receive adequate attention of the scholars and primarily about its functions and benefits to strengthening any hadiths which explicitly mentioned in the chapter. Therefore this study aims to reveal the existence of indicative hadiths by al-Tirmidhi in various books of hadith to determine its function. The study found in the chapter on marriage, there are thirty-one (31) sub chapters which contain (108) indicative hadiths, and the values are; nineteen (19) sub chapters had sahih (sound), seven (7) had hasan (good), and five (5) sub chapters in da‘if status (weak). The study also found in the chapter on sell and buy, there are fivety-three (53) sub chapters which contain (180) indicative hadiths, and the values are; thirty-neen (39) sub chapters had sahih (sound), eleven (11) had hasan (good), and three (3) sub chapters in da‘if status (weak). The study also found the existence of indicative hadiths in Sunan al-Tirmidhi serve as mutabi‘at (parralelism), and shawahid (witnesses). Hence, the implications of this study shows that those indicative hadiths in the book of Sunan al-Tirmidhi are deemed utilizable as most of them are having the status of acceptable (maqbul). This study contribute by al-Tirmdzi significantly in the future exploration of the numerous indicative hadiths found in other chapters as they are deemed as important evidence in the execution of the Islamic law who serves as mutaba'at.